The Impact of Collaborative Learning Techniques on Written Expression, Self- Regulation and Writing Motivation - Sever, Esra; Akyol, Hayati (International Electronic Journal of Elementary Education, 2023)
The study, which examined the effects of collaborative learning techniques on written expression, self-regulation and writing motivation, was designed according to the pretest - posttest control group experimental model. The research was conducted in the 2017-2018 academic year with a total of 88 students in two experimental and one control group. The first experimental group did the writing exercises according to the cooperation cooperation and the second experimental group student teams success divisions technique. The control group, on the other hand, carried out writing studies according to the Turkish Lesson Teaching Program (Republic of Turkey Ministry of National Education Board of Education and Discipline, 2018). The data were analyzed with the SPSS 22.0 program. Personal Information Form, 6+1 Analytical Writing and Evaluation Scale, Writing Oriented Self-Regulation Scale, and Writing Motivation Scale were used as data collection tools. When the findings of the research are examined, there was a significant difference between the experimental groups and the control group's posttest score averages of self-regulation skill for writing; No significant difference was found between the written expression skills and writing motivation posttest mean scores.